Prospects For The Use Of Polymer Composite Fittings In Building Structures In The Republic Of Uzbekistan - Muftoxiddin, Ashurov; Tursunalievich , Sadirov Bahrom; Mutalib Ogli Хaydarov Abduхalil; Asiljon Ogli, Ganiyev Akbar; Sobirkhon Ogli, Sodikhonov Sardorhon; Qodirali Qizi , Khaydarova Kholishon (The American Journal of Engineering and Technology, 2021)
The article discusses the prospects for the use of polymer composite fittings in building structures and the use of alternative materials to replace steel in the construction industry.